Getting the Most "Bang" for their Buck: An Assessment of Concussions on NHL Player Contracts - Habicht, Martin (Université d'Ottawa | University of Ottawa, 2012)
This paper searches for evidence that general managers are discounting players with concussions as a result of their perceived increased riskiness. By analysing new contract signings over the 2007-2011 period, I assess whether a players concussive history